Penetapan Kadar Vitamin C dalam Beberapa Varietas Buah Melon dengan Spektrofotometri - Yuni Dermawati (Program Studi S1 Farmasi, STIKES Senior, Medan, 2021)
Fruits are a type of food that contains nutrients, vitamins and minerals which are generally very good for consumption every day. Vitamin C is one of the vitamins contained in fruits. Vitamin C is a micronutrient that is indispensable for body metabolism. In addition, vitamin C also plays a role in immune function or immune. Various analyzes were carried out to determine the level of vitamin C. This study aims to determine the effect of varieties on the vitamin C content in melon fruits. Examination of vitamin content was carried out using the ultraviolet spectrophotometric method. Determination of vitamin C levels in several melon varieties by ultraviolet spectrophotometry shows that the vitamin C content in green local melons is 1.4528 mg / 100 g and the vitamin C content in orange local melons is 1.6118 mg / 100 g. Higher levels of vitamin C were found in the orange melon fruit varieties compared to the lowest levels of vitamin C in the green melon fruit varieties. This can occur because vitamin C levels are widely distributed in plants, vitamin C levels can vary due to several factors such as the variety of plants, processing, temperature, leaving a long time open to air (oxidation), harvesting time, storage, and the latter is where it grows. There were differences in vitamin C levels in several varieties of melon which was determined by ultraviolet spectrophotometry. The highest vitamin C content is in orange melon.